2021
DOI: 10.1038/s41419-020-03378-w
|View full text |Cite
|
Sign up to set email alerts
|

M2-like macrophages exert hepatoprotection in acute-on-chronic liver failure through inhibiting necroptosis-S100A9-necroinflammation axis

Abstract: Necroptosis has emerged as a novel and crucial player in acute and chronic liver diseases. Necroptotic cells lead to the release of DAMPs including S100A9, followed by the development of necroinflammation. We previously have documented the beneficial hepatoprotection conferred by M2-like macrophages in acute-on-chronic liver failure (ACLF) in vitro and in vivo, namely, M2-like macrophages protect hepatocytes against apoptosis. Herein, we integrated necroptosis, S100A9, and necroinflammation into this hepatopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 39 publications
3
40
1
Order By: Relevance
“…LPS/D-GalN-injected mice used as an ALF model in this study are also referred to as models for fulminant liver failure (FLF), acute liver injury (ALI), and acute hepatitis. Previous studies reported that liver damage in LPS/D-GalN-injected mouse models is induced by multiple complex mechanisms, such as inflammation, apoptosis, necrosis, autophagy, pyroptosis, necroptosis, and ferroptosis [14][15][16][17][18][19]. However, most previous studies using LPS/D-GalN-injected mouse models analyzed one or two of the mechanisms mentioned above and reported that many hepatoprotectants proposed in those studies modulate the analyzed mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LPS/D-GalN-injected mice used as an ALF model in this study are also referred to as models for fulminant liver failure (FLF), acute liver injury (ALI), and acute hepatitis. Previous studies reported that liver damage in LPS/D-GalN-injected mouse models is induced by multiple complex mechanisms, such as inflammation, apoptosis, necrosis, autophagy, pyroptosis, necroptosis, and ferroptosis [14][15][16][17][18][19]. However, most previous studies using LPS/D-GalN-injected mouse models analyzed one or two of the mechanisms mentioned above and reported that many hepatoprotectants proposed in those studies modulate the analyzed mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…GSDMD is a pore-forming protein that promotes pyroptosis and the release of pro-inflammatory cytokines [43]. GSDMD-mediated hepatocyte pyroptosis extends the inflammatory response to ALF by upregulating monocyte chemotactic protein 1/CC chemokine receptor-2 to recruit macrophages [17,18]. YA pre-administration also decreased the upregulation of GSDMD, caspase 1 activation, C-terminal of GSDMD cleavage in the LPS/D-GalN induced ALF model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum S100A12 may reflect the oxidative stress and inflammation levels of HBV-ACLF patients, and an increase in S100A12 may be an important biological index of poor prognosis ( 58 ). Others have found that M2 macrophages can alleviate liver injury and play a protective role in ACLF mice by inhibiting the S100A9 protein-related necrotic inflammation axis, which provides new insight for the treatment of ACLF patients ( 98 ). In addition, in children with pediatric acute liver failure (PALF), the serum S100 β level may correlate positively with the severity of the disease ( 94 ).…”
Section: Types and Functions Of Damps Related To Aclfmentioning
confidence: 99%
“…Septic liver injury, as a common clinical feature, is regarded as an independent indicator of mortality [ 4 ]. In addition, liver dysfunction is strongly associated with poor survival of sepsis patients; damaged hepatocytes could release damage-associated molecular patterns to trigger systemic inflammatory responses, exacerbating the dysfunction of the liver and other organs [ 5 ]. Therefore, effective protection of liver function is crucial for the treatment of sepsis and the improvement of patient prognosis.…”
Section: Introductionmentioning
confidence: 99%